Fruit Fly (Diptera: Tephritidae) Populations on Same Fruit Crops in Sumuri District, Bintuni Bay - Susiamti, Widi; Panjaitan, Rawati; Binur, Robi (Manunggal Halim Jaya, 2024)
Most of the people of Sumuri District make a living as farmers, especially fruit and vegetable farmers. Local fruit plants that are commonly cultivated include bananas, papaya, mangoes, oranges, rambutan, pineapple and water guava. One of the obstacles experienced by the community is the presence of pests that attack the fruit, causing poor fruit and even crop failure. This prompted a field survey of fruit flies in community fruit plantations. The field survey was conducted in October-December 2023 in Tofoi Village, Materabu Jaya Village and Forada Village, Sumuri District, Bintuni Bay. The survey was conducted using the trapping method with Steiner model traps that have been modified from mineral water bottles and the addition of native fruit samples and Methyl Eugenol (ME) with petrogenol trademark. Traps were set for three days and then identification and collection of fruit fly samples were carried out. The results showed that the highest population of fruit flies was in pineapple (Annanas commosus), which was 738 and the least in water guava (Syzygeum aqueum), which was 324. There were nine fruit fly species identified from this study, including: Bactrocera umbrosa (Fabricus), B.carambolae (Drew and Hancock), B.dorsalis (Hendel), B.curreyi (Drew), B.curvifera (Walker), B.emittens (Walker), B.papayae (Drew and Hancock), B.tryoni (Froggatt) and Procecidochares connexa (Macquart)